Submission based direct funding : does it concur with the principles of empowerment? : a thesis presented in fulfilment of the requirement for the degree of Master of Philosophy in Development Studies at Massey University - Gardner, Caroline (Massey University, 2000)
After a review of recent developmental writings, it can be concluded that an effective system for encouraging and promoting endogenous development is yet to be fully articulated in both development practice and theory. It is proposed in this thesis, that SBDF presents an alternative and effective distribution system for small community run project/programmes compared to that which is currently being employed by the majority of ODA agencies. SBDF is based around the idea of partnership between local and international development agencies, this model situates the donor in the role of facilitator to endogenously directed development. SBDF can be described as a system where local groups plan, design and implement projects with the support of a donor agency. This paper analyses the SBDF system used by the Canada Fund (CF) in Samoa to fund small community-run projects. This funding system differs from other small funding programmes in a number of important ways: • The fund is actively made available to vulnerable subgroups within the community. The CF utilises networking and 'cold-calling' to access these groups. This proactive approach to disseminating information about the fund is specific to the CF. • The CF provides support throughout the project process where this is required, thereby ensuring that organisational capacity building is an ongoing and organic process. • A partnership is created between the donor and the local organization. This is defined by open dialogue between both partners throughout all stages of the project and the necessity for local partners to contribute resources and finance to the project; thereby ensuring local ownership of projects. The study concluded that the SBDF model embodies much of the current theoretical thinking on empowerment, which places emphasis on the need for the primacy of endogenous control in the project process. A number of problems with the SBDF are recognised and recommendations are made for the improvement of the system, namely in regard to how local groups can increase their capacity in the areas of monitoring and accountability with the assistance of the donor agency.
Keywords: Community development; Economic assistance; International development; Funding programmes